International Terrorism and Global Response: An Appraisal - Opukri, Chris. O; Ebienfa, Kimiebi Imomotimi (American Journal of Humanities and Social Sciences, 2013)
<!–[if gte mso 9]> <![endif]–> International Terrorism as it appears is the scourge of all nations in the globe. There is no particular nation that is shielded from its effects either in terms of a germane threat or outright infliction of destruction. The responses from the said menace have led to what is currently termed as “the war on terror”, an approach that creates collateral damages of its own. This paper in the first instance, has examined the concept “war on terror” and its legal justifications and ramifications. While the military can engage in fighting wars, it is not quite correct to christen some conflicts as war on terror because we cannot conquer terror through war. War on terror can only lead to destruction of property and human suffering and cannot usher peace and stability. Finally, the authors are of the view that arbitrations, negotiations, diplomatic sanctions and economic embargo, could serve as a better option for peace and security than military expeditions. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>